Video Game Content Regulation and the Politics of Implementation: The Indonesia Game Rating System, 2016–2026 - Evan Andhika Suci (Journal of Political Innovation and Analysis, 2026)
Indonesia has approximately 81 million active gamers and a gaming market valued at USD 1.79 billion in 2023, yet Peraturan Menteri Komunikasi dan Informatika Nomor 11 Tahun 2016 produced no operational video game content classification system for nearly eight years. The Indonesia Game Rating System (IGRS), relaunched through Peraturan Menteri Komunikasi dan Informatika Nomor 2 Tahun 2024 and anchored in Peraturan Pemerintah Nomor 17 Tahun 2025 on child protection in electronic systems (PP TUNAS), nominally positions Indonesia as the first country in Southeast Asia with a dedicated national game rating scheme a claim whose operational substance remains contested following the suspension of the Steam integration in early 2025. This article analyzes why the regulatory gap persisted between 2016 and 2024 and what interests shaped its eventual resurgence. Through documentary analysis of regulatory instruments, ministerial public statements, and secondary academic literature, the study identifies four explanatory variables: limited state enforcement capacity, asymmetric market power between national regulators and transnational platform operators, low political salience, and the absence of a compelling public legitimation frame. IGRS's post-2024 relaunch reflects changed political framing rather than resolution of the structural conditions that produced the original implementation gap. The findings contribute a Southeast Asian case to comparative literature on platform governance in developing economies and apply a political economy framework to video game content regulation for the first time in this regional context.